Doing well and good : the human face of the new capitalism - Friedland, Julian (Ethics in practice (Greenwich, Conn.), 2009)
Ethical business creates social value. That's the theme of this bold new volume, heralding and defending this rapidly-growing new conception of capitalism making its way into the mainstream. It provides clear and succinct guidelines for how to evaluate what counts as an ethical business as well as how and why ethical businesses tend to succeed better over the long term. The book is jargon-free and targeted primarily at thought leaders and academics in business and philosophy who will want to use it in their business ethics classes. Each chapter has been selected for its ability to engage a wide audience without oversimplifying the content. All twelve chapters are original and authored by leading business ethicists including William Shaw, Tony Simons, Duane Windsor, and Mark Schwartz. Each piece makes use of recent empirical evidence or ethical theory (or both) in order to present a detailed yet overarching picture of what ethical business looks like--and how to achieve it--in today's global environment. It is thus divided into three subsections: 1. The Role of Corporate Culture 2. A New For-Profit Paradigm 3. Making the Change Happen: Voluntary and Regulatory Examples Perhaps the book's greatest strength is its blending of cutting-edge philosophy, psychology, and management theory into a cohesive, provocative, and accessible format. Hence, it promises to launch a wide discussion of what exactly we should expect the moral duty of business to be.